To dance : a memoir - Siegel, Siena Cherson; Siegel, Mark (New York : Aladdin Paperbacks, 2006)
Follows the life and career of a ballerina, detailing her dance school experiences, performances, and personal life. Presented in graphic novel format.
Cover title: To dance, a ballerina's graphic novel.
Booklist starred
Notable/Best Books (A.L.A.)
School Library Journal
Booklist starred, September 2006
Bulletin (Center for Children's books), January 2007
Keywords: Ballerinas -- Fiction; Ballet -- Fiction; Cartoons and comics; Ballerinas -- Fiction; Ballet -- Fiction; Comic books, strips, etc; Graphic novels